2001
DOI: 10.1053/jhep.2001.24237
|View full text |Cite
|
Sign up to set email alerts
|

Malaria sporozoites actively enter and pass through rat Kupffer cells prior to hepatocyte invasion

Abstract: Malaria sporozoites have to cross the layer of sinusoidal liver cells to reach their initial site of multiplication in the mammalian host, the hepatocytes. To determine the sinusoidal cell type sporozoites use for extravasation, endothelia or Kupffer cells, we quantified sporozoite adhesion to and invasion of sinusoidal cells isolated from rat liver. In vitro invasion assays reveal that Plasmodium berghei and P. yoelii sporozoites attach to and enter Kupffer cells, but not sinusoidal endothelia. Unlike hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 72 publications
(103 reference statements)
2
155
1
2
Order By: Relevance
“…To cross the sinusoid, sporozoites may migrate through or between the endothelial cells [46] or they may use Kupffer cells as a gateway to the underlying hepatocyte, a hypothesis put forward after sporozoites were observed inside Kupffer cells at early time points after injection [47]. More recent in vitro observations of the interaction between sporozoites and sinsusoidal cells found that sporozoites preferentially associate with Kupffer cells and are capable of going through Kupffer cells to productively enter hepatocytes [48]. In addition, op/op mice which have reduced numbers of Kupffer cells have somewhat lower parasite burdens when inoculated with sporozoites by mosquito bite [49].…”
Section: To the Livermentioning
confidence: 99%
See 1 more Smart Citation
“…To cross the sinusoid, sporozoites may migrate through or between the endothelial cells [46] or they may use Kupffer cells as a gateway to the underlying hepatocyte, a hypothesis put forward after sporozoites were observed inside Kupffer cells at early time points after injection [47]. More recent in vitro observations of the interaction between sporozoites and sinsusoidal cells found that sporozoites preferentially associate with Kupffer cells and are capable of going through Kupffer cells to productively enter hepatocytes [48]. In addition, op/op mice which have reduced numbers of Kupffer cells have somewhat lower parasite burdens when inoculated with sporozoites by mosquito bite [49].…”
Section: To the Livermentioning
confidence: 99%
“…In the normal hepatic sinusoid, however, the majority of sporozoites probably gain access to the hepatic parenchyma by crossing Kupffer cells. Controversy remains as to how Kupffer cells are crossed, whether it is by a unique mechanism involving parasitophorous vacuole formation [48] or whether they traverse these cells in the same way they traverse other cells, a hypothesis suggested by the inability of SPECT 1, SPECT 2 and CelTOS knockout sporozoites to cross this barrier.…”
Section: To the Livermentioning
confidence: 99%
“…Kupffer cells are specialized macrophages and protect the liver against microbes, contaminants and other aggressions. Why these phagocytes are used as entry gate by sporozoites indeed is difficult to understand [12]. But some early studies have shown that IgA antibodies preferentially attach to hepatocytes, blocking the entry for sporozoites.…”
Section: Taurinementioning
confidence: 99%
“…Most of our views on how the parasite goes into and out of the hepatic tissue come from transmission electron microscopy approaches, whose significance is frequently limited by the small number of events reported, or from in vitro studies, which have their own limitations [7][8][9] . In recent years, imaging technology has been transferred from physics laboratories to the biological domain with impressive efficiency, which has revolutionized the way in vivo questions can be tackled 10,11 .…”
Section: Introductionmentioning
confidence: 99%